Menstruation-Related Disorders—Dysmenorrhea and Heavy Bleeding—as Significant Epiphenomena in Women With Rheumatic Diseases - Orlandi, Martina; Vannuccini, Silvia; El Aoufy, Khadija; Melis, Maria Ramona; Lepri, Gemma; Sambataro, Gianluca; Bellando-Randone, Silvia; Guiducci, Serena; Cerinic, Marco Matucci; Petraglia, Felice (Frontiers in Pharmacology, 2022)
Background: In women with rheumatic diseases (RDs) menstruation-related disorders have never been investigated. The aim of this study was to evaluate gynaecological symptoms/disorders in fertile age women with RDs. Materials and methods: All patients (n=200) filled up a self-administered questionnaire on their gynaecological history, menstrual cycle pattern, menstrual-related symptoms and quality of life (QoL). RDs group was then compared to a control group of 305 age-matched fertile age women. Results: Among patients with RDs, 58% had arthritis, 40% connective tissue diseases (CTDs) and had 1.5% systemic vasculitis. No differences were observed CTDs and arthritis, except for family history of HMB which was more common among women with CTDs (p<0.01). When compared to controls, women with RDs reported more frequently heavy menstrual bleeding (HMB) during adolescence (51.7% and 25.4%, respectively; p=0.0001) and adult life (37.7% and 25.9%, respectively; p=0.0065). Also, dysmenorrhea in adolescence was significantly more common among cases (55.6% and 45.4%, respectively; p=0.0338). Gynecological pain (dysmenorrhea, non-menstrual pelvic pain, dyspareunia, dysuria and dyschezia) in RDs patients were more frequent in comparison to controls (p=0.0001, 0.0001, 0.0001, 0.0001, 0.0002; respectively). Considering only the moderate and severe symptoms in RDs, dysmenorrhea and dyspareunia remain significantly more frequent in women with RDs in respect to controls (p=0.0001; p=0.0022; respectively). QoL scores were significantly reduced in RDs women, either in physical (p=0.0001) and mental domains (p=0.0014) of short-form 12. Conclusion: Women affected by RDs frequently presented menstruation-related disorders, thus RDs female patients should be questioned about gynaecological symptoms and referred to the gynaecologist for an accurate evaluation.